Morphology, ultrastructure and distribution of Placoneis itamoemae sp. nov. (Cymbellaceae) from Brazil - Straube, Arielli; Tremarin, Priscila Izabel; de Castro-Pires, Emanuela Cristina; Marquardt, Gisele Carolina; Ludwig, Thelma Alvim Veiga (Phytotaxa, 2013)
The analysis of samples from different Brazilian subtropical localities revealed an unknown Placoneis species. This paper describes the new species Placoneis itamoemae Straube, Tremarin & Ludwig based on valve morphology revealed with light and scanning electron microscopy. Related taxa such as Navicula clementis var. linearis Brander and Placoneis conveniens Hustedt are also compared. The new species is characterized by elliptic-lanceolate valves, rostrate apices, one to three very conspicuous isolated pores at the central area, uniseriate striae with inconspicuous areolation, and distal raphe ends deflected to opposite sides. Placoneis itamoemae was found in lotic and lentic environments of southern and southeastern Brazil.